Penyakit Karat Putih Krisan di Sekitar Bandungan, Ambarawa - Haryono Semangun; Wikan Radityo; Lilik Nurcholis; Martanto Martosupono; Djoko Murdono (Jurnal Perlindungan Tanaman Indonesia, 2010)
Chrysanthemum white rust (CWR) caused by Puccinia horiana creates severe losses on chrysanthemum (Chrysanthemum grandiflorum, Dendranthema grandiflora) in plastic houses in Bandungan (750–1050 masl.) and its surrounding. In lower elevations higher disease intensities were found around roof leakages and ventilations. In Sumowono (1000–1050 masl.) the disease was spread evenly in plastic houses. Teliospores of P. horiana develop in form of basidia (promycelia) at midnight which directly form basidiospores (sporidia). Spreading of basidiospores occur at 2 to 4 in the morning, especially at 3 a.m. Infection takes place through lower or upper surface of the leaves, as the two sides have stomata. Incubation time in this trial is 8–11 hours. Vegetative as well as generative phase of chrysanthemum have the same susceptibility. Many farmers applied inappropriate fungicides in controlling CWR. It is recommended to apply carbendazim as systemic fungicide alternated by protectant fungicides as mancozeb.